SPATIO-TEMPORAL ANALYSIS OF PEDESTRIAN TRAFFIC IN IKEJA AREA, LAGOS (2014)
In spite of the fact that vehicles and pedestrians constitute important urban traffic, conceptual explanations and investments have focused more on vehicular than pedestrian traffic and activities. This study was carried out to examine pedestrian volumes and patterns of flow, factors influencing decision to walk, and pedestrian level of safety in Ikeja, Lagos. Data on the socio- economic characteristics, landuse and street maps of Ikeja were collected from relevant ministries. Seventeen landuse zones were identified in order to examine the spatial variations in landuse type, pedestrian traffic and related activities. Buildings on identified streets were systematically selected. Random sampling was used to select heads of households in selected buildings and pedestrians. Between May and August 2009, data were collected through a questionnaire survey administered to a total of 1,205 respondents. Vehicle speed, road width and number of pedestrians that walkway width carried were recorded along all the 56 streets. Mean and standard deviation were used to present results on pedestrian traffic and walking distances; t-test and analysis of variance were used to measure respondents’ walking distance to facilities. Multiple regression was used to evaluate frequency of pedestrian trips and level of safety on roadways; logistics regression was used to estimate the decision to walk, and analytical hierarchical process was used to rank respondents choice of walkways. An average of 56,663 pedestrians walked along all the streets between 7:00am and 7:00pm; and flow pattern varies significantly ( across zones. The highest average hourly flow of pedestrians ( ̅=6,313±6,765.04) on road networks across zones was observed between 5:00-6:00pm and the lowest ( ̅ =1,788±2,277.72) was observed between 7:00-8:00am. Residential landuse (28.1%) and commercial landuse (27.7%) were the most prominent landuse types while financial landuse (10.9%) and industrial landuse (8.0%) were discreet. From 7:00am to 7:00pm, Otigba zone with highest commercial activities (48%) recorded the highest average pedestrian traffic ( ̅=18,791±5,445.59) and Mobolaji Johnson zone with the lowest commercial activities (5%) recorded the least ( ̅=509±182.46). The mean walking distances by household heads to bus stations and landuse activities was 0.244±0.02km while that of pedestrians was 2±0.10km which was significant (t=71.01, p=≤0.05). Trips to work (30.4%); religious centres (20.5%) were the most important trip UNIVERSITY OF IBADAN LIBRARY xx composition while social trips (3.3%) and visit to friends (1.3%) trips were the least. Work trips (β=0.35, t=3.82) and trips to fast food points (β=0.29, t=2.63) were the significant factors explaining frequency of pedestrian trips. Respondents’ decision to walk (e(β)=1.81) under cool weather was almost twice than when it was hot. Female respondents walk (e(β)=1.02) 1.02 times more than their male counterparts. Safety on walkways ranked highest (λ=0.44) while congestion on walkways (λ=0.04) ranked lowest in the choice of walkways. Pedestrians’ level of safety increased with distance of walkways from moving vehicles (β1=0.60, t1=5.14), but decreased with higher vehicular volume (β2=0.20, t2=1.73) and speed (β3=0.07, t3=0.76). There was a limited distance over which household heads could walk this encourages driving close to facilities thereby, creating congestion and parking problems. Increased investment through more pedestrian friendly roadways in central business districts of urban centres would enhance pedestrian mobility and safety. Keywords: Pedestrian Traffic, Safety of Walkways, Urban Centres. Word count: 499 words.